The emancipation of the language learner - Larsen-Freeman, Diane (Studies in Second Language Learning and Teaching, 2012)
The general trend in language education over the years has been to ascribe to language learners increasing power and responsibility for their own learning. While this is commendable, the autonomy of learners is still constrained by views of language that see learners as being mere “hosts” of another’s language. Such views restrict learners to roles as language learners who make errors not language users who innovate. This article argues for a more enlightened view of language and of learners, one inspired by a complexity theory perspective. It also proposes that such a perspective is respectful of learner agency.